The Effect of Teaching Materials Based on Aceh's Local Wisdom on Student Learning Results of Junior High School in Aceh Province - Mardhatillah; Verawati; Evi Eviyanti; Isda Pramuniati (Britain International for Academic Research (BIAR) Publisher, 2019)
This study aims to determine the effect of teaching materials based on local Aceh's wisdom on student learning outcomes in learning English in class VII SMP Aceh Besar. This study uses a quasi-experimental method, consisting of a control class and an experimental class. Data collection techniques using written tests. Technical data analysis with t-test. The results showed that the value of tcount = 2.664 was obtained. At the significant level α = 0.05 and dk = 35 + 35 - 2 = 68, the price of ttable = 1.669 (complete calculation in attachment 21) is obtained. By comparing tcount and ttable obtained tcount> ttable or 2.664> 1.669 means that Ha is accepted and H0 is rejected. This shows that Aceh's local wisdom-based teaching materials are effective in improving student learning outcomes in 7th grade of Aceh Besar Junior High School.